Directive Speech Acts in TikTok-Based Scholarship Mentoring: A Gender Perspective - Septi Kartika Putri; Farida Indri Wijayanti (General English Education, 2026)
This study examines directive speech acts in scholarship preparation mentoring content on TikTok, analyzes the perlocutionary effects of these speech acts, and explores differences in their use between male and female influencers. The study employs a descriptive qualitative method with a pragmatic approach. Data were collected from 11 TikTok videos uploaded by six influencer accounts that provide scholarship preparation mentoring, including three male influencers and three female influencers. The data consisted of utterances containing directive speech acts, which were interpreted based on their situational and sociocultural contexts. The results indicate that there were 107 directive utterances containing situational and sociocultural contexts, of which 69 were produced by male influencers and 38 by female influencers. The most frequently used directive speech act among male influencers was orders (31.88%), while female influencers tended to use suggestions more frequently (36.84%). These findings reveal a tendency in the selected data: male influencers prefer more explicit communication strategies, whereas female influencers tend to use more polite communication strategies. This study suggests that the use of directive speech acts in digital academic guidance content may be influenced by gender, communication goals, and the interactional context of social media.